غاستون باشلار وكوجيتو التعلم أو العقلانية المعلمة - بن زينب، شريف; دراس، شهرزاد (جامعة وهران2 محمد بن أحمد, 2020)
Gaston Bachelard (1884- 1962) was known in the scientific community as the philosopher of science, the author of many epistemological concepts, such as the epistemological obstacle, the backward history, the dialectical dialectic, his artistic contributions to the concept of fantasy and his relation to the four cosmological elements (fire, Water, air, dirt). This is why the Bashlari project is twofold, although at first glance different at first glance, but they are in fact complementary, rational, and imaginary, a project of multiple dimensions, although the most advanced epistemology and technical studies, but we stand on other fields of knowledge no less important than The remaining topics, we mean the subject of teaching and learning.
عرف غاستون باشلار Gaston Bachelard (1962-1884) في الأوساط العلمية، بفيلسوف العلم الناحت للكثير من المفاهيم الفلسفية، على غرار العقبة الابستيمولوجية، التاريخ التراجعي، الجدلية المعرفية، بالإضافة إلى إسهاماته في المجال الفني بدراسته لمفهوم الخيال وعلاقته بالعناصر الأربعة الكوسمولوجية (النار، الماء، الهواء، التراب). لهذا يعتبر المشروع الباشلاري ذو شقين، وإن ظهرا مختلفين للوهلة الأولى، إلا أنهما متكاملين في حقيقة الأمر، شق عقلاني، وشق خيالي، مشروع ذو أبعاد متعددة، وإن كانت الإبستيمولوجيا والدراسات الفنية الأكثر حضورا، إلا أننا نقف على حقول معرفية أخرى لا تقل أهمية عن بقية المواضيع، ونعني بها موضوع التعليم والتعلم.
Keywords: باشلار، غاستون، 1962 م. -- العقلانية -- الفلسفة الحديثة -- الفلسفة الفرنسية